Vasculitis associated with VEXAS syndrome: A literature review - Watanabe, Ryu; Kiji, Manami; Hashimoto, Motomu (Frontiers in Medicine, 2022)
Vasculitis is an inflammatory disorder of the blood vessels that causes damage to a wide variety of organs through tissue ischemia. Vasculitis is classified according to the size (large, medium, or small) of the blood vessels. In 2020, VEXAS (vacuoles, E1 enzyme, X-linked, autoinflammatory, somatic) syndrome, a novel autoinflammatory syndrome, was described. Somatic mutations in methionine-41 of UBA1, the major E1 enzyme that initiates ubiquitylation, are attributed to this disorder. This new disease entity connects seemingly unrelated conditions: inflammatory syndromes (relapsing chondritis, Sweet’s syndrome, or neutrophilic dermatosis) and hematologic disorders (myelodysplastic syndrome or multiple myeloma). Notably, such patients sometimes develop vasculitis, such as giant cell arteritis and polyarteritis nodosa, and fulfill the corresponding classification criteria for vasculitis. Thus, vasculitis can be an initial manifestation of VEXAS syndrome. In this research topic exploring the link between autoinflammatory diseases and vasculitis, we first provide an overview of the disease mechanisms and clinical phenotypes of VEXAS syndrome. Then, a literature review using the PubMed database was performed to delineate the clinical characteristics of vasculitis associated with VEXAS syndrome. Finally, the therapeutic options and unmet needs of VEXAS syndrome are discussed.